2018
DOI: 10.1002/lary.27521
|View full text |Cite
|
Sign up to set email alerts
|

I dream of Gini: Quantifying inequality in otolaryngology residency interviews

Abstract: Objectives Otolaryngology applicants routinely decry conflicting interview dates because this limits the number of interviews that one can attend, despite being offered an interview. Conversely, applicants also perceive that a large number of interviews are offered to a minority of applicants. We sought to verify and quantify the inequality in distribution of interviews attended. Study Design Retrospective analysis of the National Resident Matching Program (NRMP) 2016 Charting Outcomes in the Match and Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 11 publications
(24 reference statements)
1
58
1
Order By: Relevance
“…It has also been reported that 26% of OTO-HNS applicants attended 50% of interviews, suggesting that OTO-HNS programs were vying for a smaller pool of upper echelon of candidates. 14 Without external constraints, the competition for top candidates is likely to intensify. This arrangement risks unfilled programs, unmatched applicants, and less-than-ideal matches as applicant preference is unable to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that 26% of OTO-HNS applicants attended 50% of interviews, suggesting that OTO-HNS programs were vying for a smaller pool of upper echelon of candidates. 14 Without external constraints, the competition for top candidates is likely to intensify. This arrangement risks unfilled programs, unmatched applicants, and less-than-ideal matches as applicant preference is unable to be determined.…”
Section: Discussionmentioning
confidence: 99%
“… 19 The consequence of application inflation that will be of crucial importance this application cycle is the growing awareness that a small percentage of applicants has been receiving a disproportionate percentage of interview offers. 20 , 21 In the era of virtual interviews, if these applicants choose to schedule all of their interview offers, there is a real potential for detrimental downstream effects to other applicants. This may also lead to a greater number of unfilled residency spots, with a larger number of programs and applicants required to enter into the Supplemental Offer and Acceptance Program.…”
Section: Introductionmentioning
confidence: 99%
“…This may exacerbate an already appreciated issue regarding an ineffective distribution of interviews across applicants. 8 It will benefit both applicants and programs if strategies can be implemented that help ensure that interview slots are ultimately filled primarily by those applicants with a meaningful interest in a particular program. Per the 2018 National Residency Match Program "Charting Outcomes in the Match," 98% of US senior applicants from allopathic medical schools who contiguously ranked 11 or more programs successfully matched at a radiation oncology program.…”
Section: Residency Interviewsmentioning
confidence: 99%